METTL3-mediated m6A modification of ZBTB4 mRNA is involved in the smoking-induced EMT in cancer of the lung - Cheng Cheng; Yan Wu; Tian Xiao; Junchao Xue; Jing Sun; Haibo Xia; Huimin Ma; Lu Lu; Junjie Li; Aimin Shi; Tao Bian; Qizhan Liu (Elsevier, 2021)
N6-methyladenosine (m6A) is an epigenetic modification associated with various tumors, but its role in tumorigenesis remains unexplored. Here, as confirmed by methylated RNA immunoprecipitation sequencing (meRIP-seq) and RNA sequencing (RNA-seq) analyses, exposure of human bronchial epithelial (HBE) cells to cigarette smoke extract (CSE) caused an m6A modification in the 3' UTR of ZBTB4, a transcriptional repressor. For these cells, CSE also elevated methyltransferase-like 3 (METTL3) levels, which increased the m6A modification of ZBTB4. RIP-qPCR illustrated that ZBTB4 was the intent gene of YTHDF2 and that levels of ZBTB4 were decreased in an YTHDF2-dependent mechanism. The lower levels of ZBTB4 were associated with upregulation of EZH2, which enhanced H3K27me3 combining with E-cadherin promoter, causing lower E-cadherin levels and induction of the epithelial-mesenchymal transition (EMT). Further, in the lungs of mice, downregulation of METTL3 alleviated the cigarette smoke (CS)-induced EMT. Further, the expression of METTL3 was high in the lung tissues of smokers and inversely correlated with ZBTB4. Overall, our results show that the METTL3-mediated m6A modification of ZBTB4 via EZH2 is involved in the CS-induced EMT and in lung cancer. These results indicate that m6A modifications are a potential therapeutic target of lung damage induced by CS.